Combining Aqueous Solution Processing and Printing for Fabrication of Flexible and Sustainable Tin Dioxide Ion‐Gated Transistors. Issue 2 (19th August 2021) - Subramanian, Arunprabaharan; Azimi, Mona; Santato, Clara; Cicoira, Fabio
Abstract: Ion‐gated transistors (IGTs) are extensively used in chemo‐ and bio‐sensors as well as intelligent sensors, that is, with neuromorphic computing functionality, exploiting their ion to electron convertibility. Metal oxides are attractive as active channel materials in IGTs because of their low‐temperature solution processability, ambient stability, and tunable optoelectronic properties. SnO2 is a low‐cost material widely used in thin‐film transistors, gas sensors, and transparent electrodes. In this work, films of crystalline SnO2 nanorods are prepared on flexible substrates using a controlled aqueous growth technique, at 95 °C. The top contact source and drain metal contacts were patterned by either photolithography or printing. The transistor behavior of SnO2 nanorod films gated with different gating media, such as room‐temperature ionic liquids, in inert atmosphere, and aqueous saline solutions, in ambient air are studied. In addition, the transistor behavior of SnO2 IGTs in the original flat and tensile bending state are also studied. The earth abundance of tin oxide, the low energy consumption fabrication process by low‐temperature solution processing and printing, as well as, the use of an aqueous electrolyte for the gating medium make our devices extremely promising for green and sustainable electronics. Abstract : Flexible ion‐gated transistors based on crystalline SnO2 nanorods deposited via a sustainable aqueous growth technique (≈95 °C) on polyethylene terephthalate are reported. The devices operate at low voltage (≈1 V) using either an ionic liquid or an aqueous electrolyte as the ion gating medium. Top contact electrodes are patterned via photolithography or printing.